2023
DOI: 10.1088/1755-1315/1230/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, heritability, and correlation of hybrids maize agronomy characters adaptive to dry land, medium plains

K Syahruddin,
Suwardi

Abstract: The selection of hybrid maize plants that adapt to dry land in the medium plains is very important considering the very widely available such land in Indonesia, so the existence of adaptive varieties is needed. Information on agronomic characters of adaptive hybrid maize is the basic information for character selection to make the breeding program more effective. The study aims to determine the genetic variability, heritability, and correlation of hybrid maize agronomic characters tested in dry land of medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Except for plant height and stem-leaf angle, the mean values of other traits showed minimal differences between the years, indicating stable identification in this environmental context. The diversity analysis results demonstrated that the test material exhibits higher levels of phenotypic diversity, aligning with the findings of Ma et al [36] and Meng et al [26], but diverging from those of Sirlene Viana d.F [37] and Syahruddin K [38]. These discrepancies are likely due to variations in environmental conditions, climate, cultivation practices, and germplasm resource origins.…”
Section: Diversity Of Phenotypic Traits In Maize Promotes Selection O...supporting
confidence: 86%
“…Except for plant height and stem-leaf angle, the mean values of other traits showed minimal differences between the years, indicating stable identification in this environmental context. The diversity analysis results demonstrated that the test material exhibits higher levels of phenotypic diversity, aligning with the findings of Ma et al [36] and Meng et al [26], but diverging from those of Sirlene Viana d.F [37] and Syahruddin K [38]. These discrepancies are likely due to variations in environmental conditions, climate, cultivation practices, and germplasm resource origins.…”
Section: Diversity Of Phenotypic Traits In Maize Promotes Selection O...supporting
confidence: 86%